Stable Europium(III) Complexes with Short Linkers for Site‐Specific Labeling of Biomolecules. Issue 6 (4th September 2017) - Faschinger, Felix; Ertl, Martin; Zimmermann, Mirjam; Horner, Andreas; Himmelsbach, Markus; Schöfberger, Wolfgang; Knör, Günther; Gruber, Hermann J.
Abstract: In this study, two new terpyridine‐based Eu III complexes were synthesized, the structures of which were optimized for luminescence resonance energy‐transfer (LRET) experiments. The complexes showed high quantum yields (32 %); a single long lifetime (1.25 ms), which was not influenced by coupling to protein; very high stability in the presence of chelators such as ethylenediamine‐ N, N, N ′, N ′‐tetraacetate and ethylene glycol‐bis(2‐aminoethylether)‐ N, N, N ′, N ′‐tetraacetic acid; and no interaction with cofactors such as adenosine triphosphate and guanosine triphosphate. A special feature is the short length of the linker between the Eu III ion and the maleimide or hydrazide function, which allows for site‐specific coupling of cysteine mutants or unnatural keto amino acids. As a consequence, the new complexes appear particularly suited for accurate distance measurements in biomolecules by LRET. Abstract : The missing link : Highly stable Eu complexes possessing long emission lifetimes and high quantum yields are prepared. A unique feature of these complexes is the combination of a short linker with bioorthogonal coupling functions, which brings the Eu III probe very close to the attachment site on the biomolecule and reduces systematic errors upon measuring intra‐ and intermolecular distances by luminescence resonance energy transfer.